Strengthening The Implementation of The Independent Curriculum For Teachers In Min 2 Bogor: Penguatan Implementasi Kurikulum Merdeka Bagi Guru di Min 2 Bogor - Kristiawan, Nana; Ramadhan, Putri Utami; Utami, Amaira (Universitas Lancang Kuning, 2025)
The independent curriculum workshop provides teachers with an understanding of the concept of implementing the independent curriculum as well as experience in compiling teaching modules at MIN 2 Bogor. This service methodology uses a workshop approach. The workshop lasted for 1 day with several stages including; (a) Field observations; (b) coordination with partners, (c) program outreach; (d) program implementation and (e) evaluation. The results of the workshop evaluation showed that there was an increase in the understanding of MIN 2 Bogor teachers and education staff who were categorized as good from 12.50% to 37.50%, while those who had sufficient knowledge from 12.50% to 18.75% and those who had sufficient knowledge less decreased from 75.00% to 43.75%. This shows that providing materials and assistance with teaching modules can increase the understanding of teachers and education staff. The Independent Curriculum Workshop Program contributes to increasing the competence of teachers in the professional field and opens up opportunities for further training on the theme of preparing educational assessments and educational supervision. Thus, this workshop succeeded in preparing teachers to answer future educational challenges.